BLENDED LEARNING READINESS AND ITS WAY FORWARD: THE CASE OF UNDERGRADUATES OF UNIVERSITI UTARA MALAYSIA (Practitioner Research, 2021)
Currently, majority of students in the higher education institutions are millenials and they are very synonyms with the information and communication technology.  Therefore, HEIs should apply a modern way of delivering knowledge to the students such as blended learning. Blended learning is a combination of face-to-face and online learning method in teaching and learning process. The objective of this study is to determine the readiness of undergraduates in public universities towards blended learning. Data was collected from 283 undergraduates from Universiti Utara Malaysia using questionnaire and was analysed descriptively. The result shows that majority of the students aware of blended learning method, have the necessary skills to participate and have participated in the blended learning. Overall, the students are ready to embark into the blended learning approach. The study provides insights in understanding the current state of studentsâ€™ preparedness towards blended learning in the university.